If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7x + 7) = 252 Reorder the terms: 3(7 + 7x) = 252 (7 * 3 + 7x * 3) = 252 (21 + 21x) = 252 Solving 21 + 21x = 252 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 21x = 252 + -21 Combine like terms: 21 + -21 = 0 0 + 21x = 252 + -21 21x = 252 + -21 Combine like terms: 252 + -21 = 231 21x = 231 Divide each side by '21'. x = 11 Simplifying x = 11
| (W+1)(2w-3)=5 | | 5=3k-2k | | Log(x)=9 | | 3x+4x+5=3 | | D+4.7=2.8t(7.4) | | 6(7m+3)= | | 3x+4x-5=3 | | -0.2x(-0.07)= | | 9b=4b-25 | | 7x+1=8x+16 | | 1650-25h=1325 | | 6x-3x=-6+5x | | 5(x-7+4)=34 | | -20x-8+7=-5 | | .23=log(x) | | 3x-4x-5=3 | | y-7=(x+4) | | 2(x+4)+2(x)=4(x+2) | | 3x-4x+5=-3 | | 3b=10-b | | 5(3x+7)=35 | | 3*-5+12-5*-5=22 | | -12=-15x | | 3x+4x-5=-3 | | 7x+5=44-6x | | -11+9-y=4y+3 | | 5(3x+7)=72 | | -6(5m-8)=-162 | | 147=3(1+6p) | | 14x-6-6=-2 | | (8y-4)-(2y-1)= | | 3x+12-5x=-2(x-5) |